Interpretation of Public Figures in Indonesian Law Number 7 Of 2012 Concerning Handling Social Conflicts in The Perspective of Legal Certainty - Rayno Dwi Adityo (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2022)
Handling social conflicts can involve elements of the community, one of which is the involvement of community leaders as part of peacemakers and their position is recognized in the law on handling social conflicts. However, the definition of community leaders is still not clear. This article aims to analyze the meaning of community leaders in the law for handling social conflicts in terms of the principle of legal certainty. This article is based on normative juridical research with a literature research scheme. The result shows that the formulation of the concept of understanding community leaders has not fulfilled the element of legal certainty. A clear definition of community leaders will help determine the extent to which the limits of their authority are protected by law. This study also offers additional materials for those who have the authority to be able to make efforts to improve.